SINGAPURA DAN ASEAN: ANALISIS RELASI NEGARA DAN INSTITUSI KAWASAN DI TENGAH PANDEMI COVID-19 - Riska Putri Hariyadi (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2020)
Increased interstate connectivity has led to the mobility of the COVID-19 outbreak easily spread throughout the world, including Southeast Asia. This outbreak has a multi-dimension effect that encourages countries to take two possibilities, Collaboration to handle the outbreak or by issuing restrictions as protection measures. Through this paper, the author describes the relations that occur in the Southeast Asian region by analyzing Singapore and ASEAN in the face of the outbreak. This paper argues that Singapore and ASEAN show commitment to the handling of the COVID-19 outbreak through regional cooperation such as the Asean COVID-19 Response Fund and solidarity actions with member countries. COVID-19, Singapura, ASEAN, Regional Cooperation